Effects of intraoperative oxidated regenerated cellulose on wound healing reaction after glaucoma filtration surgery: A comparative study with Interceed and Surgicel - Nuray, Akyol; Nusret, Akpolat (Wolters Kluwer Medknow Publications, 2008)
Background: The successful lowering of the intraocular pressure after glaucoma filtration surgery depends mostly on the nature of the healing response, which is also the single most important modifiable factor. Aims: To evaluate and compare the effectiveness of two oxidated regenerated cellulose material, Interceed and Surgicel on wound healing reaction after glaucoma filtration surgery. Setting and Design: University hospital, prospective study. Materials and Methods: Full thickness filtration surgery was carried out on three groups of rabbits. Interceed and Surgicel was applied in Groups 1 and 2 respectively. The third group was the controls. Intraocular pressure, anterior chamber depth and bleb appearance were checked on the first, third, seventh and 14(th) days. The rabbits were sacrificed on the 14(th) day and the trabeculectomy area with overlying conjunctiva was excised fixed, stained and evaluated histopathologically. Statistics: The values obtained from the clinical and histopathologic evaluation were statistically analyzed using non-parametric tests (Mann Whitney-U and Kruskall Wallis tests) in SPSS for Windows v-10. P values under 0.05 for statistical significance in comparisons were considered significant. Results: The groups were similar with respect to intraocular pressure, anterior chamber depth, bleb appearance and number of the fibroblasts and neutrophils on the seventh and 14(th) days. Mean number of the eosinophils and vessels was significantly less in Groups 1 and 2 (P = 0.014, P = 0.20 respectively). Macrophages in Group 2 were significantly less than Group 1 (P = 0.047). Conclusion: Both these agents seem to suppress vascularization. Since they have no significant effect on fibroblast proliferation, it is controversial to talk about wound healing modulation.
Keywords: glaucoma filtration surgery; interceed; surgicel; wound healing